Kinked Silicon Nanowires: Superstructures by Metal-Assisted Chemical Etching - Sandu, Georgiana; Avila Osses, Jonathan; Luciano, Marine; Caina, Darwin; Stopin, Antoine; Bonifazi, Davide; Gohy, Jean-François; Silhanek, Alejandro; Florea, Ileana; Bahri, Mounib; Ersen, Ovidiu; Leclère, Philippe; et al. (Nano letters, 2019)
We report on metal-assisted chemical etching of Si for the synthesis of mechanically stable, hybrid crystallographic orientation Si superstructures with high aspect ratio, above 200. This method sustains high etching rates and facilitates reproducible results. The protocol enables the control of the number, angle, and location of the kinks via successive etch-quench sequences. We analyzed relevant Au mask catalyst features to systematically assess their impact on a wide spectrum of etched morphologies that can be easily attained and customized by fine-tuning of the critical etching parameters. For instance, the designed kinked Si nanowires can be incorporated in biological cells without affecting their viability. An accessible numerical model is provided to explain the etch profiles and the physicochemical events at the Si/Au–electrolyte interface and offers guidelines for the development of finite-element modeling of metal-assisted Si chemical etching.